DESKRIPSI USAHATANI TANAMAN BUMBU MASAK â€œRAMPA-RAMPA CAMPURâ€ DAN SALURAN PEMASARAN DI DESA SEA DAN KOTA MANADO - Soleman ., Yapri; Nordy F. L. Waney; Jen ., Tatuh (AGRI-SOSIOEKONOMI, 2017)
This study aims to describe the cultivation of seasoning plants "rampa-rampa mix" andmarketing channels that occur in the Village Sea and the city of Manado. This research was conducted in September 2016 until October 2016. The data used are primary data and secondary data. The primary data collection was conducted by direct interview technique with 40 (forty) respondents in this case seasoning plants "rampa-rampa campur" and also using written data in the form of documents obtained from the village head. The data obtained was analyzed using descriptive analysis and presented in the form of story or table. The results of thisstudy indicate that the average profit of cooking season is Rp.461.104 in 1 (one) time to make asale.